Analisis Pembelajaran dalam Jaringan (Daring) Mata Pelajaran Bahasa Arab Siswa Kelas 4D Sekolah Dasar Muhammadiyah Gisting - Rudis Septian; Hamdal Zakaria; Heriansyah (Program Studi Pendidikan Bahasa Arab, 2021)
The research is based on the effectiveness of the application of new learning methods that are widely practiced in Indonesia, namely the online learning system. The background of this research is the mandatory use of online learning methods regarding the spread of the Covid-19 virus. So that all educational institutions regardless of whether or not they are able to implement online learning are forced to use online learning methods. This research aims to find out how the online learning process of Arabic language subjects. The subjects of this study were the students of class 4D at SD Muhammadiyah Gisting, totaling 27 people. The method that researchers use is descriptive qualitative, the data collection techniques that researchers use are observation, documentation and questionnaires. The results of this study are more than 50% of parents and students feel that this online learning method is ineffective and does not provide satisfactory results, and there are many hopes that learning will return to using the old learning method due to the many problems experienced by teachers, parents and students during this online learning. The biggest problem is the unequal ownership of online learning facilities, students who come from various economic circles result in some students not having facilities that must be used in online learning, some others have to share with family members who also have a need for these facilities. So based on the results of the research that the researcher has done, the researcher concludes that teachers, parents and students agree that online learning methods are not effectively used in Arabic language learning, especially at Muhammadiyah Gisting Elementary School.